Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I see the following sequence and it's: $$h=1+4+4^2+\cdots+4^{X+Y}=\frac{4^{X+Y+1}-1}{4-1}$$

how we get this sequence?

I know this is a primary question but I confused :)

share|cite|improve this question
Do you mean, how does one prove the formula for the sum of terms? – Travis Aug 24 '14 at 16:55
Dear @Travis, I means how get this? – Mouna Mokhiab Aug 24 '14 at 16:56
up vote 2 down vote accepted

This is an example of a geometric series. Let's say we try to sum: $$S=1+r+r^2+r^3+\dotsb+r^n$$ In your example, $r=4$, and $n=X+Y$.

There is a well known "trick" for solving this. Multiply by $r$: $$Sr=r+r^2+r^3+\dotsb+r^n+r^{n+1}$$ Notice how this is the same thing as $S$, except without the $1$ at front and with an extra $r^{n+1}$ at the end. In fact: $$Sr=S-1+r^{n+1}$$ Solving: \begin{align} Sr&=S-1+r^{n+1} \\ Sr-S&=-1+r^{n+1} \\ S(r-1)&=r^{n+1}-1 \\ S&=\frac{r^{n+1}-1}{r-1} \end{align}


Plugging in $r=4$ and $n=X+Y$, we get your answer.

share|cite|improve this answer
can we say sum is: $((4^{X+Y+1}-1)/3)-1?$ – Mouna Mokhiab Aug 24 '14 at 17:28
No. Why do you have the $-1$ at the end? It should just be: $$\frac{4^{X+Y+1}-1}{4-1}=\frac{4^{X+Y+1}-1}{3}$$without any $-1$s at the end. (If you were summing $4+4^2+\cdots+4^{X+Y}$ rather than $1+4+4^2+\cdots+4^{X+Y}$, then sure.) – Akiva Weinberger Aug 24 '14 at 17:33
you means $4+...+4^X+Y=((4^{X+Y+1}-1)/3)-1 $ am I right? – Mouna Mokhiab Aug 24 '14 at 17:35
Yes. If we were to start with $4+\dotsb$ rather than $1+4+\dotsb$, then you would have to subtract off the $1$. However, in your Original Post, you asked the question with the $1$. – Akiva Weinberger Aug 24 '14 at 17:37
yes, thankssss so muchhhhh – Mouna Mokhiab Aug 24 '14 at 17:38


share|cite|improve this answer
would you please add more detail ? – Mouna Mokhiab Aug 24 '14 at 17:01
@MounaMokhiab – kingW3 Aug 24 '14 at 17:02

This is a GP, where $a= $ first term=$1$, $r=$common ratio=$4$

Sum of GP is given by $\frac{a(r^n-1)}{r-1}$

$1+\hspace{25 pt}X+Y\hspace{30 pt}$=n=Number of terms

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.